2012
DOI: 10.1590/s0102-695x2011005000169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a plant origin drug on the biodistribution of 99mTc-DTPA in Wistar albino rats

Abstract: Abstract:In recent years all over the world, medicinal plants are used quite a lot but side effects of biological and chemical contents and radiopharmaceutical interactions for each consumer in question aren't entirely well-known. The studies of plant origin drug interaction with radiopharmaceuticals are highly relevant and desired. One of them is passiflora syrup (Passiflora incarnata L., Passifloraceae) which is widely used for depression, insomnia, anxiety and menopause period. The aim of current study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The pharmacological interaction process affects the biodistribution of the radiopharmaceutical due to the mechanism of action of the, toxicological interaction, pharmacokinetic interaction, and physical properties of the drug (Iii, et al, 1982). The latest research by Zora et al found that the administration of medicinal plants affected the biodistribution uptake of [ 99m Tc]Tc-DTPA in the kidney and bladder (Zora et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological interaction process affects the biodistribution of the radiopharmaceutical due to the mechanism of action of the, toxicological interaction, pharmacokinetic interaction, and physical properties of the drug (Iii, et al, 1982). The latest research by Zora et al found that the administration of medicinal plants affected the biodistribution uptake of [ 99m Tc]Tc-DTPA in the kidney and bladder (Zora et al, 2012).…”
Section: Introductionmentioning
confidence: 99%